A vertigem das antologias: Gregório de Matos - Santos, Ciro Soares dos (2017)
The infinity of anthologies: Gregório de Matos thesis is a compilation with a list of covers, poems, verses, notes, themes and dates taken as data for supporting the thesis that the baroque poet constitutes himself as an artist author from the anthological practice since always. The simplicity of this assertion hardly hides the complexity of demonstrating, therefore, that, from his poetic discourse in the Portuguese colony to the canonization in Brazilian literature, there is a historical movement of reading the Gregório de Matos‘ works, which repeats itself: the leading of an author from the unapprehensible immensity to the partial unitary in books; whose cycles of anthologies emerge according to which the integrated chapters of this study are organized. An approach to the anthological practice faces the problematic of describing the story about Gregório de Matos‘ establishment as an author via crystalized poetic reception of anthological publications. The research enables the accomplishment of the general objective on understanding the reception of the poet‘s work about the reflection on different reading embodiments promoted-propitiated by anthologies. From the selected books set reading, after collecting them in bookshops and libraries, we have come to the inferential considerations on the anthological practice from the cover to the paratexts. Therefore, we take off from the general question on the work‘s reception of the sixteenth-century writer, documented by anthologists, as from the general hypothesis that the editions of the Gregorian work was conditioned by the historical determinants from each reception period. To verify this hypothesis, we observe the current anthologies in front of the reading horizon of Gregorian‘s legacy, propitiated by the poetic making of when it was published and also by the current theoretical presuppositions of art studies in the seventeenth century. This procedure is operated through a dialogue with the critical fortune dedicated to the seventeenth-century author, mainly the Haroldo de Campos and Augusto de Campos‘ criticism to the Gregorian legacy, as well as the Francisco Ivan‘s essay on baroque poetry, in addition to Adolfo Hansen and Marcello Moreira‘s research on colonial letters. The infinity of anthologies reaffirms the literature history‘s importance on aiming to review the poetic legacy‘s judgment in different periods, according to the social circumstances from each time and Gregorio de Matos‘s work understandment from romanticism to modernism, until contemporaneity. Francisco Adolfo de Varnhagen, Segismundo Spina, James Amado, Hélio Pólvora, Gilfrancisco, André Seffrin, Iuri Pereira, João Adolfo Hansen and Marcello Moreira are editors‘ names of Gregório de Matos‘ poetry. They are responsible for bringing the anthological cycles to life and for carrying on the seventeenth-century poetries‘ anthological practice for brazilian readers.